Association of metabolic and inflammatory molecule levels and post-covid syndrome of varying severity - A. A. Karaseva; A. D. Afanaseva; E. V. Garbuzova; E. V. Kashtanova; Ya. V. Polonskaya; E. M. Stakhneva; V. S. Shramko; L. V. Shcherbakova; I. I. Logvinenko; Yu. I. Ragino (Бюллетень сибирской медицины)
Aim. To study the associations of the levels of metabolic and inflammatory molecules and the severity of postCOVID syndrome (PCS) in COVID-19 convalescents.Materials and methods. The observational cross-sectional study included 270 individuals aged 18–84 who were COVID-19 convalescents, including 191 patients with PCS of whom 97 patients had mild PCS and 94 had moderate PCS. Serum concentrations of metabolic and inflammatory molecules were determined using enzymelinked immunosorbent assay (ELISA), including: alpha interferon (IFN-α), interleukin 1 beta (IL-1β), interleukin 6 (IL-6), interleukin 8 (IL-8), monocyte chemoattractant protein 1 (MCP-1), insulin, C-peptide, and high-sensitivity C-reactive protein (hs-CRP).Results. In COVID-19 convalescents with PCS of varying severity, the level of IL-6 was 1.3 times higher than in individuals without PCS. Among men with PCS, the levels of IL-6, MCP-1, and hs-CRP were 1.5, 1.2 and 1.9 times higher, respectively, compared with men without PCS. In men with moderate PCS, the level of IL-6 was 1.9 times higher and hs-CRP was 1.7 times higher than in men without PCS. The risk of having moderate PCS in COVID-19 convalescents was directly associated with the concentration of C-peptide in the blood. In men, the risk of having PCS was directly associated with the concentration of hs-CRP in the blood.Conclusion. In COVID-19 convalescents, the risk of having moderate PCS is directly associated with the level of C-peptide in the blood. In men, the risk of having PCS is directly associated with the level of hs-CRP in the blood.